Sistem Informasi Manajemen pada PT. Andalas Bioteknologi Saiyo Padang - Dahlan, Dahniel; Maulana, Ilham Tri; Yanto, Gusrino; Faisal, Joe (Jurnal Teknologi dan Informasi (JATI), 2019)
PT. Andalas Biotechnology Saiyo Padang is a company engaged in providing medical materials and equipment. In carrying out its business services, the administration process of the company has not used software specifically in the form of management information systems. A company certainly has a company data processing report. At present the data processing is still manual, resulting in not optimal performance of PT. Andalas Saiyo Biotechnology Padang. With the creation of a new management information system, it will be able to provide fast and appropriate output for the decision making process. The system development method used in this research is the waterfall method and uses Unified Modeling Language (UML) tools. Management information systems are developed with a website-based framework, using the PHP programming language (Pear Hypertext Preprocessor) and MySQL database as a database server. The final result of this research is the creation of a management information system of PT. Saiyo Padang Andalas Biotechnology that can help employees manage Company data that is well-systemized.